2022
DOI: 10.1186/s12909-022-03839-0
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression and their interdependent influencing factors among medical students in Inner Mongolia: the cross-sectional survey

Abstract: Background Mental health has become a global problem, among which anxiety and depression disorder were ranked as the first and sixth leading causes of disability, respectively, according to the World Health Organization (WHO). Medical students experienced higher levels of anxiety and depression than the general population. But there was a lack of research on the emotional situation among medical students in Inner Mongolia. The main objectives of this study were to investigate the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Additionally, the scores for depression were significantly lower among only-child college students compared to their non-only-child counterparts. These findings align with prior research [17] , indicating that college students who are only-children typically receive greater parental care, do not engage in competitive dynamics with siblings, have lower levels of stress, and exhibit comparatively reduced levels of depression. The scores pertaining to system logic and illness conception among college students in higher vocational colleges exhibited a statistically significant increase compared to students in undergraduate institutions.…”
Section: 2demographic Differences In the Variablessupporting
confidence: 88%
“…Additionally, the scores for depression were significantly lower among only-child college students compared to their non-only-child counterparts. These findings align with prior research [17] , indicating that college students who are only-children typically receive greater parental care, do not engage in competitive dynamics with siblings, have lower levels of stress, and exhibit comparatively reduced levels of depression. The scores pertaining to system logic and illness conception among college students in higher vocational colleges exhibited a statistically significant increase compared to students in undergraduate institutions.…”
Section: 2demographic Differences In the Variablessupporting
confidence: 88%
“…The SAS score of our participants was 43.26 ± 8.88, which was higher than the norm in China. We compared the result with that in other populations [18,19]. In one study, which was designed to explore the alterations of functional connectivity in subregions of the basal forebrain, 96 healthy controls were included and the SAS score was 33.46 ± 2.69 [18].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, which was designed to explore the alterations of functional connectivity in subregions of the basal forebrain, 96 healthy controls were included and the SAS score was 33.46 ± 2.69 [18]. Another study aimed to investigate the prevalence of anxiety among medical students in Inner Mongolia (China); the average SAS score of 1187 students was 39.60 ± 7.81 [19].…”
Section: Discussionmentioning
confidence: 99%
“… 29 Study has also shown that the SAS has good reliability and validity (Cronbach’s α=0.75 and Kaiser-Meyer-Olkin=0.86, respectively). 30 …”
Section: Methodsmentioning
confidence: 99%